A Comparison of the Types of Problems Encountered by Entrepreneurial Students and Successful Professional Entrepreneurs. (July 2019) - Reeves, Philip M.; Zappe, Sarah E.; Follmer, D. Jake
Research examining the similarities and differences between the types of problems that students enrolled in entrepreneurship courses encounter and the types of problems that successful entrepreneurs encounter when working on ventures is limited. Providing projects and activities that closely resemble real-world situations would likely increase the amount of knowledge and skills that students are able to transfer from school into the workforce. In this article, 7 successful professional entrepreneurs and 32 students enrolled in entrepreneurial classes were interviewed and asked to describe the problems that they encountered when working on projects. Fifteen different types of problems were classified based on the interviews. Entrepreneurs did not encounter three types of problems that students struggled with. Students encountered all but three of the same types of problems as entrepreneurs; but within these types of problems, there were some qualitative differences between the two groups. Implications and suggestions for improving courses and activities in entrepreneurship education are discussed.